An ANALYSIS OF VALUE ADDED TAX IMPOSITION ON VIRTUAL GOODS - Sumilat, Milan; Warongan, Jessy D.L; Korompis, Claudia W.M (ACCOUNTABILITY, 2025)
This research aims to find out how Value Added Tax (VAT) is imposed on digital goods transaction.This research uses a qualitative descriptive method by utilizing primary data and secondary data. The research results show: a) VAT collection on digital goods transactions is carried out when the transaction takes place with a tariff of 11%, and the company issues an order receipt after the transaction is successful. The Ministry of Finance specifically appointed 171 domestic and foreign companies as VAT collectors on digital goods with criteria that must be met. b) VAT payments on digital goods transactions are made every month by attaching the required files. From the results obtained, 157 companies have deposited VAT on time and experienced no delays; However, 14 collection companies were found that had not deposited VAT. c) VAT reporting on digital goods transactions is carried out quarterly by collectors by attaching files in accordance with applicable regulations. Keywords: Imposition of Tariffs, Virtual Goods, Value Added Tax